Pendidikan berbasis data: Sebuah pendekatan strategis untuk perbaikan nilai Indeks Pembangunan Manusia (IPM) Kalimatan Barat - Simbolon, Nurmala Elmin; Kalimaintan, Donald Marua (JURNAL BORNEO AKCAYA, 2019)
West Borneo's rank of human development index (HDI), which currently is one of the five ithe lowest position of all of Indonesia, requires attention from all parties. Education, one of the indicators assessed in this HDI, certainly has an important role. Vocational education, which produces skilled and ready-to-work graduates, has a big role in accelerating West Borneo's human development. This article aims to examine the importance of implementing evidence-based education or orginally evidence-based practices (EBPs) especially in vocational education. The implementation of evidence-based education can bridge the gap between the findings of research in the field of education and the practice of education in the field or school. The study in this article is qualitative research, which uses documents as information or data to be analyzed. Findings show that the mapping of the number of vocational education institutions and existing industries was very necessary to conduct. In addition, collaboration between local researchers and academics, the world of industry and local governments has a high urgency to do.